2017
DOI: 10.1053/j.gastro.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Occult Hepatitis C Virus Infection in Patients Who Achieved a Sustained Virologic Response to Direct-Acting Antiviral Agents for Recurrent Infection After Liver Transplantation

Abstract: Occult infection with the hepatitis C virus (HCV) is defined as the presence of the HCV genome in either liver tissue or peripheral blood monocytes (PBMCs), despite constant negative results from tests for HCV RNA in serum. We investigated whether patients who maintained a sustained virologic response 12 weeks after therapy (SVR12) with direct-acting antiviral (DAA) agents for recurrent HCV infection following liver transplantation had occult HCV infections. We performed a prospective study of 134 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 19 publications
5
66
0
Order By: Relevance
“…Elmasry et al . reported that all patients with OCI had unfavorable rs12979860 genotypes, whereas the ones without OCI had favorable IFNL3 rs12979860 CC or CT genotypes . In contrast, Bartolomé et al .…”
Section: Discussionmentioning
confidence: 92%
“…Elmasry et al . reported that all patients with OCI had unfavorable rs12979860 genotypes, whereas the ones without OCI had favorable IFNL3 rs12979860 CC or CT genotypes . In contrast, Bartolomé et al .…”
Section: Discussionmentioning
confidence: 92%
“…A surprising finding was chronic active inflammation in liver tissue biopsy samples from 4 patients who did not have steatosis and did not respond to corticosteroids. This form of histologically proven post‐SVR chronic active hepatitis has been infrequently reported in the IFN‐free era and has recently been attributed to the post‐transplant setting to occult HCV infection . Three patients were diagnosed with autoimmune hepatitis.…”
Section: Discussionmentioning
confidence: 97%
“…A few studies reported OCI in blood donors, in some high‐risk groups (haemophiliac and haemodialysis patients) and subjects with cryptogenic liver disease . A recent study demonstrated OCI in patients who achieved a sustained virological response to IFN‐free antiviral therapy for recurrent infection after liver transplantation . No data are actually available in support of OCI in patients with lymphoma.…”
Section: Association Between Occult Hcv Infection and Haematological mentioning
confidence: 99%